A high-gain two-stage amplifier using low-temperature poly-si oxide thin-film transistors with a Corbino structure. Issue 4 (2nd October 2022) - Jeon, Dong-Hwan; Jeong, Won-Been; Park, Jeong-Soo; Chung, Hoon-Ju; Lee, Seung-Woo
Abstract : This paper proposes a complementary metal–oxide–semiconductor (CMOS) amplifier using low-temperature poly-Si oxide (LTPO) thin-film transistors (TFTs). The Corbino structure used in the proposed amplifier has a higher output resistance than conventional amplifiers. The proposed circuit is composed of two CMOS inverters, one CMOS switch, and one input capacitor. It was possible to determine the operating point where the voltage gain could be kept high, regardless of the device variation, by shorting the gate input and output of the first amplifier. The alternating current component of the input signal was increased because the input signal was transferred to the first amplifier via the capacitor. The function of the second amplifier was to increase the total voltage gain. When a peak-to-peak voltage sine wave of 2 mV was applied at a frequency lower than 500 Hz, the proposed circuit showed an average voltage gain of 60.6 dB, which is the highest among the previously published TFT amplifiers.